"Put Myself Into Your Place": Embodied Simulation and Perspective Taking in Autism Spectrum Disorders. Issue 4 (7th February 2015) - Conson, Massimiliano; Mazzarella, Elisabetta; Esposito, Dalila; Grossi, Dario; Marino, Nicoletta; Massagli, Angelo; Frolli, Alessandro
<x xml:space="preserve">Abstract</x> Embodied cognition theories hold that cognitive processes are grounded in bodily states. Embodied processes in autism spectrum disorders (ASD) have classically been investigated in studies on imitation. Several observations suggested that unlike typical individuals who are able of copying the model's actions from the model's position, individuals with ASD tend to reenact the model's actions from their own egocentric perspective. Here, we performed two behavioral experiments to directly test the ability of ASD individuals to adopt another person's point of view. In Experiment 1, participants had to explicitly judge the left/right location of a target object in a scene from their own or the actor's point of view (visual perspective taking task). In Experiment 2, participants had to perform left/right judgments on front‐facing or back‐facing human body images (own body transformation task). Both tasks can be solved by mentally simulating one's own body motion to imagine oneself transforming into the position of another person (embodied simulation strategy), or by resorting to visual/spatial processes, such as mental object rotation (nonembodied strategy). Results of both experiments showed that individual with ASD solved the tasks mainly relying on a nonembodied strategy, whereas typical controls adopted an embodied strategy. Moreover, in the visual perspective taking task ASD participants had more difficulties than controls in inhibiting other‐perspective when directed to keep one's own point of view. These findings suggested that, in social cognitive tasks, individuals with ASD do not resort to embodied simulation and have difficulties in cognitive control over self‐ and other‐perspective. Autism Res2015, 8: 454–466. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.